Sb 5s2 lone pairs and band alignment of Sb2Se3: a photoemission and density functional theory study. Issue 36 (26th August 2020) - Don, Christopher H.; Shiel, Huw; Hobson, Theodore D. C.; Savory, Christopher N.; Swallow, Jack E. N.; Smiles, Matthew J.; Jones, Leanne A. H.; Featherstone, Thomas J.; Thakur, Pardeep K.; Lee, Tien-Lin; Durose, Ken; Major, Jonathan D.; et al.
Abstract : Lone pair Sb 5s orbitals are identified at the valence band maximum of Sb2 Se3 bulk crystals using photoemission and density functional theory. The resulting band alignments are determined and implications for solar cell applications are discussed. Abstract : The presence of a lone pair of 5s electrons at the valence band maximum (VBM) of Sb2 Se3 and the resulting band alignments are investigated using soft and hard X-ray photoemission spectroscopy in parallel with density functional theory (DFT) calculations. Vacuum-cleaved and exfoliated bulk crystals of Sb2 Se3 are analysed using laboratory and synchrotron X-ray sources to acquire high resolution valence band spectra with both soft and hard X-rays. Utilising the photon-energy dependence of different orbital cross-sections and corresponding DFT calculations, the various orbital contributions to the valence band could be identified, including the 5s orbital's presence at the VBM. The ionization potential is also determined and places the VBM at 5.13 eV below the vacuum level, similar to other materials with 5s 2 lone pairs, but far above those of related materials without lone pairs of electrons.